L-fuzzifying topological vector spaces - Cong-Hua Yan; Cong-Xin Wu (International Journal of Mathematics and Mathematical Sciences)
The main purpose of this paper is to introduce a concept of L-fuzzifying topological vector spaces (here L is a completely distributive lattice) and study some of their basic properties. Also, a characterization of such spaces in terms of the corresponding L-fuzzifying neighborhood structure of the zero element is given. Finally, the conclusion that the category of L-fuzzifying topological vector spaces is topological over the category of vector spaces is proved.